Penanaman Moderasi Islam Untuk Siswa Madrasah Ibtidaiyah - Luthfiyah, Lujeng (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
Indonesia is a multicultural country. In such a country Islamic moderation is the right choice. The cultivation of Islamic moderation must begin since children are in the elementary school phase (Madrasah Ibtidaiyah). In this phase, the doctrinal information conveyed to them is deeply embedded in their souls. It would not be strange if then their attitude at the next level was the fruit of the information and inculcation of values ​​that they got when they were at MI. Therefore, all MI teachers must master the verses about moderation, and be in line with efforts to shape the personality of the students for that purpose.